AES DUKPT Implementation at Software Point of Sale: Enhancing the Security of Digital Payment Systems - Dhingra, Raghav (Journal of Global Economy, Business and Finance, 2025)
This paper explores the implementation of the Advanced Encryption Standard (AES) with Derived Unique Key Per Transaction (DUKPT) in Software Point of Sale (SoftPOS) systems. The rapid advancement of digital payment technologies necessitates robust and efficient encryption methods to ensure secure transactions. By integrating AES DUKPT, SoftPOS systems can achieve enhanced security, scalability, and compliance with industry standards. This paper delves into the architecture, key management, encryption processes, and performance evaluation of AES DUKPT within SoftPOS environments.